Disappearance and fading in Vittorio Sereni’s Stella variabile (inOpera Esercizi di lettura su testi contemporanei, 2025)
Pier Vincenzo Mengaldo spoke of the «nihilism of the last Sereni» (in his article Il solido nulla, 1986), insisting on the images of silence, omission, lack and nothingness. Starting from Mengaldo's comment, our contribution aims to analyse some images of disappearance and fading present in Stella variabile. The contribution begins with an examination of the disappearance of the subject (i.e. the prefiguration of one's own death), and then dwells on forms of dissolution around the lyric subject and the fading and appearance of sound, through a reading of poems from Sereni's last collection.
Keywords: Vittorio Sereni; Stella variabile; Disappearance; Fading; Nothingness